The matter of images essays on representations - Dyer, Richard (London Routledge, 1993)
'How we are seen determines in part how we are treated; how we treat other is based on how we see them; such seeing comes from representation.'

The matter of images searches through the resonances of the term 'representation' analysing images in terms of why they matter, what they are made of and the material realities they refer to. Richard Dyer's analyses move from considerations of strongly negative representations pf 'out' groups to representations of dominant groups in society - men, heterosexuals, whites.

His discussion encompasses the eclectic texts of contemporary culture, from royalty to queens and dykes, politically correct labels, representation of Empireand films such as Gilda, Papillon and Night of the living dead.

Much has been written about images in society. The matter of images is distinctive in its commitment to writing politically about contemporary culture, while insisting on the importance of understanding the formal qualities and complexity of the images it investigates.
Includes bibliographical references and index
Keywords: Homosexuality in motion pictures; Motion pictures -- Social aspects; Stereotype (Psychology) in mass media